DESIGN SOCIAL DEVELOPMENT CENTER BASED ON BIOPHILIC ARCHITECTURE IN SURABAYA - adhinugraha, Andreas purwa; Wikantiyoso, Respati; Santoso, Imam (ARCHITENSA : Architectural Design Journal, 2025)
As a metropolitan city, Surabaya faces a range of social challenges resulting from rapid urbanization and unequal access to education, employment, and basic services. To respond to these challenges, there is a need for facilities capable of empowering communities through skills training and non-formal education. A Social Development Center based on Biophilic Architecture in Surabaya serves not only as a response to these social issues but also as a center for community capacity building. The design integrates natural elements such as vegetation, water features, natural lighting, ventilation, and sustainable materials to create comfortable and healthy spaces. This study was conducted through literature review, site analysis, and a design approach rooted in biophilic principles. The result is a conceptual design of a social center that supports education, training, and the strengthening of urban communities. Its implementation is expected to offer an innovative solution toward the development of a more sustainable and environmentally friendly city.